Endovascular Repair of Type B Aortic Dissection: Long-term Results of the Randomized Investigation of Stent Grafts in Aortic Dissection Trial - Nienaber, Christoph A.; Kische, Stephan; Rousseau, Hervé; Eggebrecht, Holger; Rehders, Tim C.; Kundt, Guenther; Glass, Aenne; Scheinert, Dierk; Czerny, Martin; Kleinfeldt, Tilo; Zipfel, Burkhart; Labrousse, Louis; et al. (Circulation. Cardiovascular interventions, 2013)
BACKGROUND—Thoracic endovascular aortic repair (TEVAR) represents a therapeutic concept for type B aortic dissection. Long-term outcomes and morphology after TEVAR for uncomplicated dissection are unknown. METHODS AND RESULTS—A total of 140 patients with stable type B aortic dissection previously randomized to optimal medical treatment and TEVAR (n=72) versus optimal medical treatment alone (n=68) were analyzed retrospectively for aorta-specific, all-cause outcomes, and disease progression using landmark statistical analysis of years 2 to 5 after index procedure. Cox regression was used to compare outcomes between groups; all analyses are based on intention to treat. The risk of all-cause mortality (11.1% versus 19.3%; P=0.13), aorta-specific mortality (6.9% versus 19.3%; P=0.04), and progression (27.0% versus 46.1%; P=0.04) after 5 years was lower with TEVAR than with optimal medical treatment alone. Landmark analysis suggested a benefit of TEVAR for all end points between 2 and 5 years; for example, for all-cause mortality (0% versus 16.9%; P=0.0003), aorta-specific mortality (0% versus 16.9%; P=0.0005), and for progression (4.1% versus 28.1%; P=0.004); Landmarking at 1 year and 1 month revealed consistent findings. Both improved survival and less progression of disease at 5 years after elective TEVAR were associated with stent graft induced false lumen thrombosis in 90.6% of cases (P<0.0001). CONCLUSIONS—In this study of survivors of type B aortic dissection, TEVAR in addition to optimal medical treatment is associated with improved 5-year aorta-specific survival and delayed disease progression. In stable type B dissection with suitable anatomy, preemptive TEVAR should be considered to improve late outcome. CLINICAL TRIAL REGISTRATION—URLhttp://www.clinicaltrials.gov. Unique identifierNCT01415804.